MANAJEMEN PENGELOLAAN DANA DESA BERDASAR PERMENDAGRI NO. 113 TAHUN 2014 - Ariyanti Rizka (BBM (Buletin Bisnis & Manajemen), 2018)
This study aims to determine the management of village fund management based onPermendagri No. 113 years 2014 in the village Pesanggarahan Wonokerto district Pekalonganregency.Data analysis technique from this research with comparative analysis. Comparative analysis isan analytical technique performed by making comparisons between the same elements, such asthis study that compares the financial management planning of Pesanggrahan village with thestandards that refer to Permendagri No.113 of 2014 About the Guidelines of Village FinancialManagement.For the financial management of Pesanggrahan Village, the village head, the village secretary,and the village treasurer have performed their duties in the management of village finances well.Where the planning stage is carried out by the village secretary, the implementation andadministration phase is carried out by the village treasurer, the reporting and accountabilitystages are carried out by the village head.Keywords: Village fund management, permendagri no 113 tahun 2014